Association of SARS-CoV-2 Infection With Serious Maternal Morbidity and Mortality From Obstetric Complications. Issue 8 (August 2022) - Metz, Torri D.; Clifton, Rebecca G.; Hughes, Brenna L.; Sandoval, Grecio J.; Grobman, William A.; Saade, George R.; Manuck, Tracy A.; Longo, Monica; Sowles, Amber; Clark, Kelly; Simhan, Hyagriv N.; Rouse, Dwight J.; et al.
Abstract : (Abstracted from JAMA 2022;327:748–759) It is well known that pregnant individuals with COVID-19 have increased risks such as admission to the intensive care unit (ICU), mechanical ventilation, and death when compared with both nonpregnant adults with SARS-CoV-2 infection and pregnant adults without SARS-CoV-2 infection. However, although COVID-19 is known to increase the risk of maternal morbidity related to the virus, the possibility for higher risk of serious morbidity from obstetric complications is not clear.